1995
DOI: 10.2105/ajph.85.12.1678
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride exposure and childhood osteosarcoma: a case-control study.

Abstract: OBJECTIVES. This study tests the hypothesis that fluoride exposure in a nonoccupational setting is a risk factor for childhood osteosarcoma. METHODS. A population-based case-control study was conducted among residents of New York State, excluding New York City. Case subjects (n = 130) were diagnosed with osteosarcoma between 1978 and 1988, at age 24 years or younger. Control subjects were matched to case subjects on year of birth and sex. Exposure information was obtained by a telephone interview with the subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 23 publications
4
25
0
1
Order By: Relevance
“…Assuming that population density in the RoI can be used as a reliable indicator of areas supplied with fluoridated drinking water, there was little evidence of a significant effect of water fluoridation on osteosarcoma incidence at any age or for either sex. These results are consistent with almost all previous work [5][6][7][8][9][10][11][12][13]. The higher incidence rate in young females in RoI (both fluoridated and non-fluoridated areas) is clearly unrelated to water fluoridation.…”
Section: Discussionsupporting
confidence: 92%
“…Assuming that population density in the RoI can be used as a reliable indicator of areas supplied with fluoridated drinking water, there was little evidence of a significant effect of water fluoridation on osteosarcoma incidence at any age or for either sex. These results are consistent with almost all previous work [5][6][7][8][9][10][11][12][13]. The higher incidence rate in young females in RoI (both fluoridated and non-fluoridated areas) is clearly unrelated to water fluoridation.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, case-control studies have not found any significant association between osteosarcoma risk and fluoridated drinking water (McGuire et al, 1991;Moss et al, 1995) or total lifetime fluoride (Gelberg et al, 1995). One exploratory analysis reported an increased risk among a subset of males exposed to fluoride in drinking water during childhood (Bassin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Human studies also show conflicting results. The majority of epidemiologic studies found no association between fluoride and osteosarcoma [15][16][17][18][19][20][21]. However, two studies found evidence of an association in males under age 20, but not in females [22,23].…”
Section: Introductionmentioning
confidence: 99%